Body image and nutritional status among female students at Universitas Prima Indonesia - Silitonga, Thesa Kristina Br.; Sibagariang, Eva Ellya; Leslie, William; Fransisca, Silva; Lubis, Ika Syani Putri; Suwarno, Suwarno; Hasya, Muhammad Nawal; Putri, Eka (Buletin Kedokteran & Kesehatan Prima, 2025)
Body image is an individual's subjective perception of their body shape and size, which can influence eating behaviour and nutritional status. This study aimed to analyse the relationship between body image and nutritional status among female students at Prima Indonesia University in 2025. A cross-sectional study was conducted with a sample of 69 female students from the 2023 cohort of the Public Health Study Programme, selected via total sampling. Body image data were collected using the Body Shape Questionnaire (BSQ), while nutritional status was assessed via anthropometric measurements of Body Mass Index (BMI). Data analysis employed the Chi-Square test with a significance level of 0.05. A total of 59.4% of respondents had a negative body image and 40.6% a positive body image. The distribution of nutritional status was: normal (62.3%), obese (18.8%), overweight (10.2%), and underweight (8.7%). Statistical analysis indicated a significant relationship between body image and nutritional status (p-value = 0.002). Respondents with a negative body image were more likely to have an abnormal nutritional status (overweight and obese) compared to those with a positive body image. There is a significant relationship between body image and nutritional status among female students. A negative body image is associated with a tendency towards abnormal nutritional status, particularly excess weight.